Northward to the moon [compact disc, unabridged] - Horvath, Polly (Random House/Listening Library, 2010)
When her stepfather loses his job in Saskatchewan, Jane and the rest of the family set off on a car trip, ending up in Nevada after improbably being given a bag full of possibly stolen money.